Practical advice for prescribing in old age. (January 2021) - Locherty, Marc; Alder, Sarah; Caslake, Robert; Mangoni, Arduino A.
Abstract: Optimizing drug therapy is an essential part of caring for older people. Prescribing in this group has unique challenges because of high interindividual variability in pharmacological response and homeostatic mechanisms, and the fact that frailty, rather than age, predicts physiological responses to external stimuli. The effects of drugs and how they are handled by the body change with increasing age. With decreasing life expectancy, drugs used for secondary prevention might not be appropriate, particularly where their adverse effects impair quality of life. The issue of polypharmacy is of particular concern in older people, who, compared with younger individuals, have more disease conditions for which therapies are prescribed. Several drugs cause harm to frail older individuals; they should be prescribed only where there is clear benefit and with regular monitoring. Unfortunately, the process of weighing the benefits and risks of drugs in this group is made more difficult by a paucity of relevant evidence. Formal criteria to identify potentially inappropriate medications have been developed, but can be cumbersome to apply and suffer from lack of flexibility for routine clinical care decisions. Regular medication review is an important part of management of this patient group. Suggested strategies for this are discussed.